Clinical Effectiveness of Perineural Liposomal Bupivacaine is Not Superior to Bupivacaine Hydrochloride for the Prevention of Postoperative Pain in Orthopedic Surgery: A Systematic Review and Meta-Analysis with Trial Sequential Analysis - Wan M; Liang X; Meng J; Wu H; Xi C (Journal of Pain Research)
Meixuan Wan,1 Xuan Liang,1 Jingwen Meng,2 Haiyao Wu,1 Chunhua Xi1 1Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Operation Center, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Chunhua Xi, Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, 1 Dongjiaominxiang Road, Dongcheng District, Beijing, 100730, People’s Republic of China, Tel +86-10-58268101, Email tr_xichunhua@163.comBackground: As a long-lasting local anesthetic, liposomal bupivacaine has become a part of certain multimodal analgesic regimens for acute postoperative pain. The objective of the present meta-analysis was to investigate the efficacy of liposomal bupivacaine in acute pain management after orthopedic surgery through peripheral nerve blocks and compare it with plain bupivacaine.Methods: The EMBASE, PubMed, Web of Science, Scopus databases, the Cochrane Central Register of Controlled Trials, and the Cochrane Database of Systematic Reviews were searched for randomized controlled trials (RCTs) published in print or online up to 11 October 2024. The primary outcomes were NRS scores and opioid consumption at postoperative 24– 72 hours. A minimum difference of 2.0 points on NRS scores or 30-mg in OME consumption was considered clinically relevant.Results: A total of 10 RCTs (782 patients) were finally included in the meta-analysis. There were significant differences in the mean NRS scores at postoperative 48 hours (MD = − 0.86, 95% CI: [− 1.19, − 0.45], P < 0.001) and 72 hours (MD = − 0.38, 95% CI: [− 0.54, − 0.21], P < 0.001). As regard to opioid consumption, there were statistical differences at postoperative 48 hours (MD = − 5.51, 95% CI: [− 9.97, − 1.06], P = 0.020) and 72 hours (MD = − 3.62, 95% CI: [− 6.04, − 1.21], P = 0.003). But none of the differences, including NRS scores and opioid consumption, met the prespecified thresholds for clinical relevance. Additional benefits of liposomal bupivacaine over plain bupivacaine were observed only in the nerve block duration (RR = 3.35, 95% CI: [1.92, 5.84], P < 0.001).Conclusion: The advantages of perineural liposomal bupivacaine over plain bupivacaine in providing analgesia after orthopedic surgery were statistically significant but not clinically relevant. Current evidence suggests that the existing RCTs are insufficient to support the idea that the perineural use of liposomal bupivacaine is clinically worthwhile in pain management after orthopedic surgery compared with plain bupivacaine.Keywords: orthopedic surgery, liposomal bupivacaine, postoperative pain, peripheral nerve block, systematic review, meta-analysis